1957
DOI: 10.1042/bj0650526
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids. 4. On the composition of hen's egg phospholipids

Abstract: 1. Free glutamic acid accumulates within Staphylococcu8 aurev, incubated in the presence of N-phosphoryl-L-glutamic acid or diethyl glutamate.2. Free glutamic acid does not accumulate within cells incubated with peptides containing glutamic acid residues unless glucose is also present. The rate of accumulation is higher when incubation takes place with a-glutamyl peptides than with y-glutamyl peptides and is affected by the rate of hydrolysis of the peptide within the cell and also by the partition coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
3
1

Year Published

1958
1958
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(69 citation statements)
references
References 18 publications
3
62
3
1
Order By: Relevance
“…Subsequently these separated fractions were chromatographed on silicic acid paper, and the percentage of sphingomyelin could then be determined (14). Secondly, aluminum oxide chromatography was used to separate the acidic phospholipids from the choline-containing phospholipids (24). The absorbant aluminum oxide (suitable for chromatography) 3 was washed five times with chloroform: methanol 1:1 (vol/vol) (C: M 1/1) in a beaker, the supernatant containing finely divided A120s being decanted each time.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently these separated fractions were chromatographed on silicic acid paper, and the percentage of sphingomyelin could then be determined (14). Secondly, aluminum oxide chromatography was used to separate the acidic phospholipids from the choline-containing phospholipids (24). The absorbant aluminum oxide (suitable for chromatography) 3 was washed five times with chloroform: methanol 1:1 (vol/vol) (C: M 1/1) in a beaker, the supernatant containing finely divided A120s being decanted each time.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphatidylcholine and phosphatidylethanolamine were prepared from egg yolk according to the procedure of Rhodes and Lea [14], and trigljceride from corn oil as described by Hirsch and Ahrens [15]. Protein was determined by the method of Lowry et al [16] with bovine serum albumin as the standard.…”
Section: Reagents Preparations and Determinationsmentioning
confidence: 99%
“…Classical methods for separating and identifying individual phospholipids (Deuel, 1957i Lovern, 1957Witt.-coff, 1951) (Freeman et al, 1957;Hanahan et al, 1957;Philipps, 195#;Rhodes and Lea, 1957) have shown that further fractionation of the phospholipids is possible by elution with chloroformmethanol mixtures. In general, the silicic acid column technique has wide application.…”
Section: Separation and Identification Of Phosphatidesmentioning
confidence: 99%